ADME predictions and molecular docking study of some compounds and drugs as potential inhibitors of COVID-19 main protease: A virtual study as comparison of computational results - Uslu, Harun; Koparır, Pelin; Saraç, Kamuran; Karatepe, Arzu Seyhan (My University, 2021)
Adenoidectomy is one of the most common surgeries performed in children. The tongue depressor is being routinely used during adenoidectomy exerts high mechanicalpressure on the tongue. We aimed to discover tongue swelling created by the compression of tongue depressor by using ultrasonography (USG) in pediatric patients whowere undertaken adenoidectomy. Thirty-four patients who were undertaken adenoidectomy were involved in the study group. In the control group, 33 patients who wereundertaken pediatric surgery were involved. The tongue surface area (TSA) measurement was achieved for two times. In the study group, TSA1 was performed immediatelyfollowing intubation, prior to the installment of the tongue depressor, TSA2 was performed following the removal of the tongue depressor however prior to extubation.In the control group, TSA1 was performed immediately following intubation, TSA2 was performed prior to extubation. An important correlation was noticed among theseverity of tongue swelling (defined as TSA2 - TSA1 ) (P = 0.000) and tongue depressor. Tongue depressor may provoke tongue swelling in adenoidectomy proceduresthat can be shown with USG. This tongue swelling seems to be a result of the pressure applied by the tongue depressor. Tongue depressor related tongue swelling maycause respiratory complications in patients with already restricted airway passage even if the patients are fully awake. The tongue swelling in pediatric patients underadenoidectomy surgeries was demonstrated for the first time in the literature by USG.
Keywords: Genel ve Dahili Tıp; Acil Tıp; Göz Hastalıkları; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme; Pediatri; Cerrahi